Pemilihan Moda Terhadap Rencana Penerapan Kebijakan Pembatasan Kendaraan Pribadi Roda Empat - Herawati, Herawati; Mutharuddin, Mutharuddin (Warta Penelitian Perhubungan, 2012)
Various solutions have been implemented by the DK! Government of to solve the problems of urban transport. However, these efforts have not been reduce private vehicle users as a cause of congestion. It is necessary to study on the selection mode of policy implementation plans prirnte Pelzicle restrictions. Mode choice method used in this study is Multinominal logic. The analysis will examine if the four transfer modes applicable policy. Those policies are congestion costs, increased taxes, increased parking fees, and fuel prices increase. From the results obtained that the implementation of four policies relating to the additional costs traveling to private vehicle users will have an impact on the shift to other modes of the motor (35.63%), railways (20:44%), and the busway (20.50%). Congestion charging at 20% will have an impact on the movement of the motor car users (27.57%), train (10.21 %), and the busway (12.35%); increase in vehicle tax rate of 20% will have an impact on the movement of the user to motor cars (26.10%), train (16.84%), and the busway (15.73%), an increase of 40% is the motor (29.52%), train (18.23%), busway (17.9%); increase in parking fees by 20% will have an impact on the movement of the motor car users (25.74%), rail (4.03%), and the busway (4.70%); increase in fuel prices 30% will have an impact on the movement of the motor car users (31.26%), rail (6.75%), and the busway (5.13%).